2018
DOI: 10.1259/bjr.20170914
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between MRI quantified small bowel motility and abdominal symptoms in Crohn’s disease patients—a validation study

Abstract: Cite this article as: Gollifer RM, Menys A, Makanyanga J, Puylaert CAJ, Vos FM, Stoker J, et al. Relationship between MRI quantified small bowel motility and abdominal symptoms in Crohn's disease patients-a validation study. Br J Radiol 2018; 91: 20170914.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…Taken together with previous publications, the reduced motility in active CD may reflect signs of increased inflammation 11,16,17 . In addition, the correlation between motility variance and symptoms in patients with high activity scores suggests that measurement of motility by MRE is most suitable for patients with active, inflammatory disease 15 . Measurement of MI or motility variance may not be an independent marker of neurogenic and/or myogenic dysmotility, but may rather reflect changes on MRE due to inflammatory activity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Taken together with previous publications, the reduced motility in active CD may reflect signs of increased inflammation 11,16,17 . In addition, the correlation between motility variance and symptoms in patients with high activity scores suggests that measurement of motility by MRE is most suitable for patients with active, inflammatory disease 15 . Measurement of MI or motility variance may not be an independent marker of neurogenic and/or myogenic dysmotility, but may rather reflect changes on MRE due to inflammatory activity.…”
Section: Discussionsupporting
confidence: 54%
“…However, the sensitivity and specificity for MI were lower in the present study of an unselected cohort, compared with selected study cohorts, and the optimal cutoffs in MI presented in a previous report could not be confirmed 6 . Our findings of absence of correlation between symptoms and MI are in accordance with Gollifer et al 15 On the other hand, that study could demonstrate a correlation between motility variance metric, values not analyzed in the present study, and the number of diarrheal stools and symptoms in subgroup analyses of patients with high activity scores 15 . Nevertheless, the concordance between subjectively observed motility reduction and MI in the present study suggests that MI still is a representative metric to assess motility.…”
Section: Discussionsupporting
confidence: 50%
“…MRI measurements of the stomach and small bowel motility have been the subject of various studies since the late 1990s [37], developing to now include automated analysis of the data generated [38]. Some of these methods have shown the potential for clinical translation, e.g., motility alternations and patient-reported symptoms [39]. MRI of the motility of the colon has only recently started to be addressed [40].…”
Section: Assessing Particle Motion In Dcm Using Peptmentioning
confidence: 99%
“…A proportion of patient data (n=28) used in the current study was also used in previous work investigating the relationship between two motility metrics (mean global motility and variance of global motility) and abdominal symptoms 6,7 .…”
Section: Patient Selectionmentioning
confidence: 99%
“…It is well established that motility is reduced in segments of bowel affected by Crohn's disease, and that this reduction is correlated with the severity of inflammation 4,5 . However recent work using automated software quantification has suggested that aberrant motility in apparently unaffected bowel, based on visual assessment, is linked to the severity of abdominal symptoms 6,7 . The ability of MRE to capture abnormal motility patterns in structurally normal bowel could prove a powerful tool in improving our understanding of gastrointestinal (GI) motility in health and disease.…”
Section: Introductionmentioning
confidence: 99%